Indicators of change during and after organized provision of support to parents of children with special needs - Igric, Ljiljana (Array, 2007)
Experiences from group work with parents of children with special needs will be presented. Paper is based on principles of Integrative Gestalt therapy (Petzold, 1988, Igrić, 2003). It was assumed that better self-understanding and work on self-development, together with instruction on effective caring techniques and sharing of opinions and experiences with other parents will enable parents of children with special needs to better understand their own children and create conditions for better coping and solving family problems. Some of the indicators of change during and after organized provision of support to parents have been measured.